1997
DOI: 10.1677/jme.0.0190015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proliferation of prostate cancer cells by a 19-nor-hexafluoride vitamin D3 analogue involves the induction of p21waf1, p27kip1 and E-cadherin

Abstract: We have synthesized and studied the ability of a series of seven novel 1 alpha,25(OH)2 vitamin D3 analogues to inhibit clonal growth of prostate cancer cells (LNCaP, PC-3 and DU-145). Addition of double and triple bonds to the C/D ring (C-16) and side chain (C-22 and C-23) as well as lengthening of the side chain were important for enhanced activity against LNCaP and PC-3. Reorientation of the side chain in the 20-epi configuration resulted in analogues that were extremely potent only against LNCaP (ED50 appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 23 publications
(36 reference statements)
5
127
0
3
Order By: Relevance
“…The same MTX treatment led to growth arrest, as measured by a complete block on cell proliferation (Figure 2A), and by the accumulation of the cellcycle inhibitor, p27/kip-1 ( Figure 2B, upper), whose upregulation correlates with growth arrest in LNCaP cells (Campbell et al, 1997). Methotrexate also promoted cellular differentiation, as measured by a significant rise in E-cadherin ( Figure 2B, middle), a marker of differentiation in the LNCaP cells (Campbell et al, 1997). The induction of the differentiation marker was MTX dosedependent ( Figure 2B, lower).…”
Section: Resultsmentioning
confidence: 97%
“…The same MTX treatment led to growth arrest, as measured by a complete block on cell proliferation (Figure 2A), and by the accumulation of the cellcycle inhibitor, p27/kip-1 ( Figure 2B, upper), whose upregulation correlates with growth arrest in LNCaP cells (Campbell et al, 1997). Methotrexate also promoted cellular differentiation, as measured by a significant rise in E-cadherin ( Figure 2B, middle), a marker of differentiation in the LNCaP cells (Campbell et al, 1997). The induction of the differentiation marker was MTX dosedependent ( Figure 2B, lower).…”
Section: Resultsmentioning
confidence: 97%
“…The inhibitory protein can inhibit the activation of CCDK complexes, then the cells are arrested in G0/G1 phase; therefore, the proliferation of tumor cells is inhibited (Campbell et al, 1997;Ylikomi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Following these studies antiproliferative effects have been demonstrated in a wide variety of cancer cell lines, including those from the prostate and breast (85)(86)(87)(88)(89)(90)(91)(92) . Thus, common models of VDR responses include MCF-7 breast cancer cells, LNCaP prostate cancer cells and CaCo2 colon cancer cells.…”
Section: Evidence Of Vitamin D Receptor Involvement In Cancermentioning
confidence: 99%